Self-Regulation of Weight After Sleeve Gastrectomy. Issue 2 (March 2018) - Madeira, Teresa; do Carmo, Isabel; Bicha Castelo, Henrique; Santos, Osvaldo
Bariatric surgery is recognized as the most effective method for achieving relevant weight loss in subjects with severe obesity. However, there is insufficient knowledge about weight self-regulation and quality of motivation in these patients. The main goal of this study was to characterize the association between the percentage of excess weight loss (%EWL) and the motivation to manage weight, at least 1 year after sleeve gastrectomy (SG). This is an observational longitudinal retrospective study. All patients corresponding to predefined inclusion criteria who underwent SG from January 2008 to July 2010 at a main general hospital were invited. A version of the Treatment Self-Regulation Questionnaire (TSRQ) was used to assess patients' quality of motivation: TSRQ concerning continuing the weight self-management program. Clinical data were collected from patients' records. Overall, 81 patients participated (16 men and 65 women, 25-64 years old). The average body mass index was significantly reduced from 45.3 ± 7.0 kg/m 2 preoperatively to 32.7 ± 6.9 kg/m 2 postoperatively. Autonomous self-regulation was higher than externally controlled self-regulation, regarding motives to keep managing weight after SG. Postoperatively, %EWL correlated negatively with external self-regulation. SG was found to be associated with the quality of motivation for losing weight. External motivations were associated with worse results. These findings support the importance of multiprofessional teams in the assessment and treatment of patients, aiming for the promotion of weight self-regulation after bariatric surgery.